1978
DOI: 10.5962/bhl.part.17243
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the crane flies (Diptera: Tipulidae) of two woodlands in eastern Kansas, with a key to the adult crane flies of eastern Kansas

Abstract: Data on geographical and ecological distribution have been compiled lor the 95 species of crane flies found in two natural areas in northeastern Kansas, the Breidenthal Reserve and the Natural History Reservation of the University of Kansas. These distributions correlate well with various major plant communities, or with specific habitats. The ranges of several species are extended significantly westward. New records for species not previously recorded within 500 miles of Lawrence, Kansas, include: Nephrotoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Notably, understandings of ‘violence’ that encapsulate the structural not only expand the descriptive scope of the term, but complicate notions of moral responsibility and individual blameworthiness. They demand a shift away from the Judaeo-Christian and socio-legal conception of personal liability that dominates, in favour of a more political kind of responsibility (Young, 2003).…”
Section: Conceptualising Sex-work Prostitution and ‘Violence’mentioning
confidence: 99%
“…Notably, understandings of ‘violence’ that encapsulate the structural not only expand the descriptive scope of the term, but complicate notions of moral responsibility and individual blameworthiness. They demand a shift away from the Judaeo-Christian and socio-legal conception of personal liability that dominates, in favour of a more political kind of responsibility (Young, 2003).…”
Section: Conceptualising Sex-work Prostitution and ‘Violence’mentioning
confidence: 99%
“…In Kansas, the species was common in bottomland woods and around a swamp, with adults found on the ground or in vegetation less than 2 ft high (Young 1978). In Michigan, this species was also abundant in floodplain woods, swamps, and adjoining wooded ecotones.…”
Section: Epiphragma (Epiphragma) Fasciapenne (Say)mentioning
confidence: 99%
“…Adults were common in bottomland forests, swamp margins, and moist thickets in Kansas (Young 1978), and the adult flight season in Kansas showed a bivoltine pattern, in May to mid-June, and mid-July to mid-September. In Pennsylvania, adults were found from early May through mid-October, with peaks in late May through early July, and again in late August (Young and Gelhaus 2000).…”
Section: Epiphragma (Epiphragma) Solatrix (Osten Sacken)mentioning
confidence: 99%
See 1 more Smart Citation
“…The adults of Geranomyia species were often found sucking nectar from flowers ( Alexander 1948 , 1967b ; Zhang et al 2016 ). Some phenological studies have shown that adults have a long period of activity; for example, adults of G. canadensis (Westwood, 1836) were active from April to September, G. communis Osten Sacken, 1860 from May to October, and G. rostrata (Say, 1823) from April to September ( Young 1978 ; Young and Gelhaus 2000 ). The habitats of adult flies have been rather frequently discussed in the literature ( Alexander 1916 , 1919 , 1920 , 1928a , 1928b , 1948 , 1964 , 1970a ; Englund 1999 ; Harrison and Barnard 1972 ; Knab 1910 ).…”
Section: Introductionmentioning
confidence: 99%